Surviving in Overijssel. An Analysis of Life Expectancy, 1812–1912. - Sander Wennemers; Hilde Bras (Historical Life Course Studies)
The rise in life expectancy is one of the main processes of social change in the 19th century. In the Netherlands, regional differences in life expectancy, and their development, were huge. Therefore, studies on average life expectancy or studies, which examine the whole of the Netherlands do not fully capture the differential determinants of this process. This study focuses on social, economic, and geographic differences in life expectancy in 19th-century Overijssel using the Historical Sample of the Netherlands (HSN). Exploiting Cox regression, the influence of several factors on life expectancy are investigated. The article shows that birth cohort, urbanisation, and gender had an important relation with life expectancy in 19th-century Overijssel, while industrialisation, religion, and inheritance customs were not associated with age at death.